IDENTIFIKASI BENTUK BIMBINGAN BELAJAR YANG EFEKTIF DAN PERAN ORGANISASI BIMBINGAN DI SEKOLAH - Takdirmin; Bulan Nur Faisah.Fs; Sahara; Siti Hanum Shalzabila; Nur Leorinzya Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning problems among students at school remain a challenge in the educational process, such as difficulties in understanding learning materials, low learning motivation, and a lack of learning independence. These conditions require the presence of guidance services that are able to assist students in overcoming learning obstacles in a systematic manner. This study aims to identify effective forms of learning guidance and analyze the role of guidance organizations in schools in supporting students’ learning success. The research method used in this study is a literature review by examining various relevant sources, including books and scientific journal articles related to learning guidance and guidance organizations in schools. The results of the study indicate that effective learning guidance includes individual guidance, group guidance, learning assistance, as well as remedial and enrichment services. In addition, the success of learning guidance is strongly influenced by the role of well-coordinated guidance organizations involving guidance and counseling teachers, homeroom teachers, subject teachers, school principals, and parents. Synergy among these elements enhances the effectiveness of learning guidance services, improves students’ academic achievement, and creates a supportive learning environment. Therefore, well-planned learning guidance supported by a strong guidance organization plays an important role in improving the quality of learning processes and outcomes in schools